Three essays on the effect of domestic inequality and global inequality on economic growth - Barasi, Fathalla, author; Tavani, Daniele, advisor; Kling, Robert, advisor; Cutler, Harvey, committee member; Kroll, Stephan, committee member (Colorado State University. Libraries, 2021)
In the preface to his Principles of Political Economy and Taxation (1817; 1951, p. 5), David Ricardo wrote that the determination of laws of distribution is the principal problem in Political Economy. One of the political economy concerns (normative economics) is the application of economic policies to maintain specific goals based on observation or economic theory describing (positive economics). Ricardo's statement points to the importance of income distribution for economic growth and implies that understanding the relationship between income distribution and economic growth is crucial for policymakers. These three essays aim to contribute to the existing literature on the effects of domestic and global inequality in income distribution on growth. By developing a theoretical model, the first paper attempts to capture the effect of domestic inequality on economic growth in a closed economy without government. The main novelty is modeling the adjustment between aggregate demand and aggregate supply when there is disequilibrium due to inequality in income distribution: such adjustment occurs via the economy's aggregate saving rate. The saving rate adjustment to disequilibrium results in an inverted U-shaped relationship between domestic inequality and growth, which has important implications for growth theory and policy. The second paper investigates recent global inequality trends by isolating its two components: between- and within-countries inequality and investigating their relationship with globalization. The main finding is that the recent decline in global inequality is mostly due to the decline in between-country inequality due mainly to the growth in income per capita for the most populated countries in the world (especially China & India). Although between-country inequality has decreased, within-country inequality has increased over the sample period. The recent increase in globalization is the main reason for the decrease in inequality between countries and the increased within-country inequality. By using a large panel dataset comprising almost all the countries globally, the third paper provides a further empirical investigation. First, it confirms the hump-shaped relation between domestic inequality and growth. Second, it finds a negative effect of international inequality on real output and consequently on demand for imports. Third, the latter result has implications on the effect of global inequality on economic growth, thus providing a further evaluation of the export-led growth hypothesis.
Keywords: economic growth; saving rate; global inequality; domestic inequality